How dentists in Egypt perceive their knowledge, attitudes, and barriers they face in providing oral healthcare to geriatric patients: a cross-sectional study - Mohamed Ashraf Hall; Rasha Ashmawy; Inas Karawia; Ramy Mohamed Ghazy (BMC, 2023)
Abstract Background Geriatric dentistry is an understudied area in dental schools in Egypt. Our study aimed to assess the knowledge and attitudes of Egyptian dentists regarding geriatric oral health and identify barriers to delivering dental care to geriatric patients. Methods We conducted an anonymous online cross-sectional study in November and December 2022, targeting dentists with varying levels of experience working in different Egyptian institutions. A 30-item questionnaire assessed the respondent's views on geriatric oral health, perceived knowledge, attitudes, and barriers. The Google form was distributed through emails and commonly used social media platforms. Results A total of 421 dentists responded to this online questionnaire. Of the respondents, 44.9% were male, 45.0% were between 20 and 29 years old, and 31.5% worked in more than one dental setting. Multivariate analysis revealed that female sex negatively affected attitude β = -1.72 [95%CI,-2.43 - -1.11]. The proportion of older patients who visited the respondents' clinics per day (11-30%) and more than 30% increased perceived knowledge [β = 1.01 (95%CI, 0.41 -1.62), β = 1.50 (95%CI, 0.71-2.22)] and attitude [β = 0.70 (95%CI, 0.06-1.40), β = 0.73 (95%, 0.13-1.61)] while decreased the perceived barriers [β = -1.10 (95%CI, -1.91 - -0.32)] respectively. On the other hand, years of experience increased perceived knowledge only after 5-10 years [β = 1.02 (95%CI, 0.04-2.10)] and after more than 10 years [β = 1.30 (95%CI, 0.21-2.70)]. Governmental work only increased perceived barriers [β = 1.33 (95%CI, 0.10-2.54)], while living in the middle and west delta decreased perceived barriers [β = -0.91 (95%CI, -2.12 - -0.01 and β = -1.33, (95%CI, -2.22 - -0.40) respectively]. Conclusions Our study highlights the need to improve the knowledge and attitudes of young dentists towards geriatric dentistry. Furthermore, working conditions in dental facilities, particularly in the government sector and Upper Egypt, need to be improved to reduce barriers to delivering dental care to geriatric patients.